(untitled) (University Heart Journal, 2021)
Background: Coronary artery disease (CAD) is predicted to be the most common cause of death globally. Early detection of coronary artery disease and adequate management can reduce CAD related morbidity and mortality. Various non-invasive procedures have been developed to diagnose CAD. Stress echocardiography, myocardial perfusion (SPECT) and cardiac MRI are accepted as useful tools for evaluation of inducible myocardial ischaemia in intermediate risk group patient documented by pre test probability. Among them exercise echocardiography is a remarkable physiological, safe, feasible and cost effective. Objective: To see the role of exercise echocardiography to predict CAD. Materials and methods: This cross sectional study was conducted in University Cardiac Center (UCC), BSMMU. This study include the patients who are appointed for exercise tolerance test (ETT). Echocardiographic wall motion study was recorded at rest and after peak exercise and analyzed to diagnosis the regional wall motion abnormality. Specific CAD was confirmed by coronary angiogram. Results: A total of 40 patients were included in the study from the patients who are appointed for ETT. Patients diagnosed as CAD has the mean age of 50.6 ± 9.7 years and majority of the patients were male (72.5%). Sensitivity, specificity, positive predictive value and negative predictive value of exercise echocardiography were 85.5%, 76.9%, 88.5% and 71.4% respectively in predicting coronary artery disease by exercise echocardiography. The predominant risk factors was hypertension (40.0%) followed by diabetes mellitus, smoking, dyslipidaemia and family H/O CAD were significantly associated with the development of CAD in the study subjects. Conclusion: Treadmill exercise stress echocardiography demonstrates high significance for diagnosis of CAD. University Heart Journal Vol. 17, No. 2, Jul 2021; 114-117